Effort–reward imbalance in the school setting: Associations with somatic pain and self-rated health. Issue 2 (March 2015) - Låftman, Sara Brolin; Modin, Bitte; Östberg, Viveca; Hoven, Hanno; Plenty, Stephanie
Aims: According to the workplace theory of effort–reward imbalance (ERI), individuals who perceive a lack of reciprocity between their effort spent at work and the rewards received in turn are at an increased risk of stress-related ill-health. It is also assumed that being overcommitted to work is linked to an increased risk of stress-related ill-health. This study applies the effort–reward imbalance model to the school setting. It aims to analyse the associations that effort–reward imbalance and overcommitment share with somatic pain and self-rated health among adolescents. Methods : Data are from the School Stress and Support Study (TriSSS), involving students in grades 8 and 9 (ages 14–16 years) in two schools in Stockholm, Sweden, during 2010 ( n =403). Information on effort–reward imbalance and health outcomes was gathered from self-report questionnaires. An adjusted short version of ERI was used. Factor analysis showed that extrinsic effort, reward and overcommitment constitute three distinct dimensions. The designed measures demonstrated sound psychometric properties both for the full sample and for subgroups. Ordered logistic regressions were conducted. Results : The analyses showed that low reward and higher overcommitment were associated with greater somatic pain and poorer self-rated health. Furthermore, effort–reward imbalance was linked with an elevated risk of somatic pain and poorer self-rated health. Conclusions : Students are more likely to experience stress-related ill-health when they perceive an imbalance between their effort and rewards. In addition, high overcommitment is associated with an increased risk of ill-health among students.